2009
DOI: 10.4067/s0718-19572009000200006
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplanktonic primary production modulated by coastal geomorphology in a highly dynamic environment of central Chile

Abstract: Resumen.-La circulación asociada a surgencias costeras tiene un efecto regional sobre la comunidad fitoplanctónica (i.e. aumento de las tasas fotosintéticas, incremento en biomasa), pero su influencia a escalas espaciales locales es menos clara. A una escala local (cientos de metros) y bajo condiciones de surgencia, zonas de retención con altos niveles de producción primaria (PP) tienden a ocurrir en el lado protegido de pequeñas penínsulas inducidas por la orientación, geometría, tamaño y geomorfología genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
(34 reference statements)
1
3
0
1
Order By: Relevance
“…From a perspective of maternal investment on offspring, more specific studies are required to unravel the close mechanisms that link DNA methylation to lipid metabolism in the early ontogeny of marine invertebrates. Nevertheless, this trend of increasing methylation with latitude also followed the general pattern of productivity along the coast evidenced in our climatologies, which is mostly driven by the influence of wind-driven coastal upwelling events near Punta de Tralca (PT) (Palma et al 41 ) and Los Cuervos (CU) beach in San Vicente Bay 42 and the influence of nutrients loading from Valdivia River estuary near Los Molinos (LM) 43 and the Gulf of Ancud (AN) 44 . Although we did not measure the productivity of kelp forests as food supply for T. dentatus in upwelling www.nature.com/scientificreports/ sites, different studies have shown that macroalgae grow faster and attain larger biomass in association with the upwelling sites off Central Chile 28,29 .…”
Section: Discussionsupporting
confidence: 74%
“…From a perspective of maternal investment on offspring, more specific studies are required to unravel the close mechanisms that link DNA methylation to lipid metabolism in the early ontogeny of marine invertebrates. Nevertheless, this trend of increasing methylation with latitude also followed the general pattern of productivity along the coast evidenced in our climatologies, which is mostly driven by the influence of wind-driven coastal upwelling events near Punta de Tralca (PT) (Palma et al 41 ) and Los Cuervos (CU) beach in San Vicente Bay 42 and the influence of nutrients loading from Valdivia River estuary near Los Molinos (LM) 43 and the Gulf of Ancud (AN) 44 . Although we did not measure the productivity of kelp forests as food supply for T. dentatus in upwelling www.nature.com/scientificreports/ sites, different studies have shown that macroalgae grow faster and attain larger biomass in association with the upwelling sites off Central Chile 28,29 .…”
Section: Discussionsupporting
confidence: 74%
“…In Chile primary production of plankton on opposite sides of small peninsulas can differ significantly (Henríquez et al 2007). However, these patterns can be extremely variable over time (Palma et al 2009). As a way to minimize this possible effect, we sampled along both the exposed and protected sides of small peninsulas in open access areas.…”
Section: Discussionmentioning
confidence: 99%
“…Although more recently an opposite pattern has been described whereas the weakening of upwellingfavorable winds favors the retention, along exposed sides of small headlands, of phytoplankton and associated primary production (Palma et al 2009). Since larvae of N. crockeri are vertically distributed in surface waters and feed on microplankton (mostly copepod eggs, copepods and tintinids, Balbontín et al 1997), protected sites around headlands along central Chile are optimal locations where the feeding success and larval growth of N. crockeri can occur.…”
Section: Discussionmentioning
confidence: 99%